1996
DOI: 10.1021/js960080y
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Induced Denaturation of Proteins during Freezing and its Inhibition by Surfactants

Abstract: In this study, we found that the denaturation of proteins during freezing is closely related to surface-induced denaturation. Several proteins with varying sensitivities to freezing were tested, and the results were compared with susceptibilities to surface denaturation in unfrozen aqueous solution. Also, the influence of the surfactant Tween 80 on the denaturation of each of the proteins was examined during freeze-thawing, as were the effects of Tween 80 and several other surfactants on the stability of lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
228
1
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 408 publications
(248 citation statements)
references
References 16 publications
14
228
1
5
Order By: Relevance
“…It should be noted that, among different agents/treatments capable of inducing protein unfolding, only repeated freeze and thawing cycles reproduced the modification of Stx1 responsible for the loss of PMN binding activity with preserved toxic activity (Table 1). This is consistent with the strong cor- relation between the tendency of a protein to freeze denature and its tendency to surface denature (44).…”
Section: Discussionsupporting
confidence: 85%
“…It should be noted that, among different agents/treatments capable of inducing protein unfolding, only repeated freeze and thawing cycles reproduced the modification of Stx1 responsible for the loss of PMN binding activity with preserved toxic activity (Table 1). This is consistent with the strong cor- relation between the tendency of a protein to freeze denature and its tendency to surface denature (44).…”
Section: Discussionsupporting
confidence: 85%
“…20 Our data show that surfactant (Tween 20) addition is not obligatory since process losses (includes any freeze- and surface-induced denaturation) were minimal and the post reconstitution stability data (includes any aggregation upon reconstitution) showed that reconstituted HSRV04D5, lacking Tween 20, retains its potency during storage not only at 5°C and at controlled room temperatures (≤25°C) but also when frozen at −70°C and thawed.…”
Section: Discussionmentioning
confidence: 68%
“…The denaturation during freezing is greater when proteins are frozen under conditions that generate a relatively large ice surface area. The observed results indicate that the freezing rate is an important factor that determines the integrity of lyophilized porous SF membranes 11,23 .…”
Section: Resultsmentioning
confidence: 85%
“…The freezing step plays a crucial role in the damage incurred by proteins during lyophilization. The chosen method for freezing dictates ice crystal morphology, which influences protein aggregation, primary and secondary drying rates, extent of product crystallinity, and surface area of the lyophilized product 11,12 . Several methods have been developed to manufacture threedimensional porous SF fibroin scaffolds for application in tissue engineering, including freeze-thawing 1 , salt leaching 13,14 , electrospinning 15 , and freeze-drying 16 .…”
Section: Introductionmentioning
confidence: 99%